2017
DOI: 10.7567/jjap.56.025601
|View full text |Cite
|
Sign up to set email alerts
|

Trapping and diffusion kinetic of hydrogen in carbon-cluster ion-implantation projected range in Czochralski silicon wafers

Abstract: We investigated the diffusion behavior of hydrogen in a silicon wafer made by a carbon-cluster ion-implantation technique after heat treatment and silicon epitaxial growth. A hydrogen peak was observed after high-temperature heat treatment (>1000 °C) and silicon epitaxial growth by secondary ion mass spectrometry analysis. We also confirmed that the hydrogen peak concentration decreased after epitaxial growth upon additional heat treatment. Such a hydrogen diffusion behavior has not been reported. Thus, we der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
61
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 35 publications
(62 citation statements)
references
References 41 publications
1
61
0
Order By: Relevance
“…In addition, our previous study demonstrated that the dissociation activation energy of H to dissociate from the projection range of a C-cluster is 0.76 AE 0.04 eV [4]. This activation energy is extremely close to the binding energy of the C-H 2 defect and the activation energy for the diffusion of H molecules from tetrahedral interstitial sites and multivacancy [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations
“…In addition, our previous study demonstrated that the dissociation activation energy of H to dissociate from the projection range of a C-cluster is 0.76 AE 0.04 eV [4]. This activation energy is extremely close to the binding energy of the C-H 2 defect and the activation energy for the diffusion of H molecules from tetrahedral interstitial sites and multivacancy [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 82%
“…We have developed proximity gettering technology with carbon (C)-cluster ion-implanted silicon (Si) epitaxial wafers for advanced complementary metaloxide-semiconductor (CMOS) image sensors [1][2][3][4]. Previous studies demonstrated that carbon-cluster ion implanted silicon epitaxial wafers have three characteristics suitable for high-performance CMOS image sensors [1][2][3][4]: a high gettering capability, an oxygen diffusion barrier effect and a hydrogen (H) passivation effect. In particular, we have reported the diffusion behaviour of H in the projection range of C-cluster implantation [4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…14,15) Third, a passivation effect on process-induced defects is expected owing to the hydrogen in the carboncluster ions trapped in the implanted region during the device fabrication process. 16,18) However, the formation behavior of the implantation defects considered to be the gettering sinks in the implanted region around the projection range of the carbon clusters is unclear.…”
Section: Introductionmentioning
confidence: 99%